Hallonland vid Östra Eneby prästgård: – att identifiera bärodling i det arkeologiska materialet - Kegel, Karolina (META – Historiskarkeologisk tidskrift, 2025)
Raspberry cultivation beds at the vicarage of Östra Eneby – identifying cultivation of berries in the archaeological material. Although berry seeds are commonly found as macrofossil remains in archaeological contexts, cultivation of berries can rarely be confirmed. It is generally believed that berry gardening was established in Sweden during the 17th century, becoming widespread in the 18th century. However, this dating is uncertain, partly due to source-critical issues surrounding the deposition, preservation and interpretation of plant macrofossils. In 2024, the vicarage of Östra Eneby, including its gardens, was excavated as part of the extensive contract archaeological project in Pryssgården, Norrköping, Östergötland County. Part of the garden remains, oddly located at the front of the main building, included several structures with parallel lines of spade cultivation traces and ditches filled with animal bones. Using a combination of methods and sources, including archaeological analysis of the recorded contexts, macrofossil analysis, osteology, and archival studies, the structures were identified as plant beds for berry bushes, most likely raspberries. This berry garden was probably established between 1860 and 1917, and is, to the best of our knowledge, the only archaeologically documented instance of raspberry cultivation in Sweden. Despite the relatively recent dating, the finding is relevant as an example of how cultivation of berries can be archaeologically identified.